2014
DOI: 10.1111/hepr.12362
|View full text |Cite
|
Sign up to set email alerts
|

A novel integrated Model for End‐Stage Liver Disease model predicts short‐term prognosis of hepatitis B virus‐related acute‐on‐chronic liver failure patients

Abstract: HBV-ACLF patients are characterized by high short-term mortality, but steady long-term survival. A modified MELD model by incorporating age and HE score has better predictive value of 3-month mortality than other conventional models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
0
27
1
Order By: Relevance
“…In a previous study, we have demonstrated chronic liver failure-sequential organ failure assessment (CLIF-SOFA) criteria to be better than APASL criteria in defining ACLF. 8 Various scoring systems like ChildTurcotte-Pugh (CTP), 9 model for end-stage liver disease (MELD), 10 integrated MELD (iMELD) score, 11 acute physiology and chronic health evaluation (APACHE II), 12 and CLIF-SOFA score 8 have been used for prediction of mortality in ACLF. Studies across the globe have shown increased mortality and worse prognosis in patients of cirrhosis presenting as ACLF.…”
mentioning
confidence: 99%
“…In a previous study, we have demonstrated chronic liver failure-sequential organ failure assessment (CLIF-SOFA) criteria to be better than APASL criteria in defining ACLF. 8 Various scoring systems like ChildTurcotte-Pugh (CTP), 9 model for end-stage liver disease (MELD), 10 integrated MELD (iMELD) score, 11 acute physiology and chronic health evaluation (APACHE II), 12 and CLIF-SOFA score 8 have been used for prediction of mortality in ACLF. Studies across the globe have shown increased mortality and worse prognosis in patients of cirrhosis presenting as ACLF.…”
mentioning
confidence: 99%
“…) . MELD score was the most commonly used scoring system, which was used in 24 studies (28 cohorts) involving 4663 patients . Followed by CPT score, which was used in 12 studies (16 cohorts) involving 2226 patients .…”
Section: Resultsmentioning
confidence: 99%
“…This finding was consistent with some other studies. [24,25] AFP is generally regarded as a biomarker of hepatocellular carcinoma and embryonal cell cancer, while it also rises transiently in benign acute or chronic liver injury. Some studies have found the highest concentration of cellular AFP in hepatocytes in front of the necroses.…”
Section: Discussionmentioning
confidence: 99%